2017
DOI: 10.5370/jeet.2017.12.2.601
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Control of Frequency Fluctuation and Battery SOC in a Smart Grid using LFC and EV Controllers based on Optimal MIMO-MPC

Abstract: -This paper proposes a simultaneous control of frequency deviation and electric vehicles (EVs) battery state of charge (SOC) using load frequency control (LFC) and EV controllers. In order to provide both frequency stabilization and SOC schedule near optimal performance within the whole operating regions, a multiple-input multiple-output model predictive control (MIMO-MPC) is employed for the coordination of LFC and EV controllers. The MIMO-MPC is an effective modelbased prediction which calculates future cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The PHEV model is represented as first-order transfers function with very small time constant T PHEV as shown in Figure 5(a) [24][25][26][27]. The change of PHEV output power ∆P PHEV for charging or discharging is selected according to the control signal U i of the controller.…”
Section: Plug-in Hybrid Electric Vehicle Modelmentioning
confidence: 99%
“…The PHEV model is represented as first-order transfers function with very small time constant T PHEV as shown in Figure 5(a) [24][25][26][27]. The change of PHEV output power ∆P PHEV for charging or discharging is selected according to the control signal U i of the controller.…”
Section: Plug-in Hybrid Electric Vehicle Modelmentioning
confidence: 99%
“…During the last decade, the PHEVs are being considered by several authors for their proposed load frequency control (LFC) studies with various controllers [7][8][9][10][11][12][13][14][15][16][17][18][19]. In [7] authors suggested a conventional PI/ PID controller, in [8] an adaptive control method, in [9] authors proposed a robust PI controller, in [10] a coefficient diagram method, in [11] a generalized model predictive controller (MPC), in [12] with H ∞ controller, etc. In [13][14][15][16][17] the authors proposed various optimization techniques for secondary LFC with PHEVs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, The MPC weights are tuned by PSO in Pahasa and Ngamroo but for pitch angle and PHEV controls. In Pahasa and Ngamroo, the input and output weights of a multiple‐input and multiple‐output MPC are optimized by using PSO. In Yang et al, a multivariable generalized predictive control is applied on an isolated microgrid with electric vehicles and distributed generations for LFC.…”
Section: Introductionmentioning
confidence: 99%